The successful influence of teaching ethics on Malaysian accountancy students / Conor O’Leary and Shafi Mohamad - O’Leary, Conor (Accounting Research Institute (ARI) & Faculty of Accountancy, 2008)
The Malaysian accounting profession is committed to promoting education that results in a strong ethical culture within accountants. However, some consider ethical training unproductive since trainees may have their ethical values formed pre-commencement. This paper investigates the impact of ethics instruction on final year accounting students, the future accountants of Malaysia.